Analisis Penyebaran Berita Hoax di Media Sosial: Perspektif Hukum dan Peran Masyarakat dalam Mitigasi - Masrufah, Masrufah; Fatmawati, Nynda (Universitas Muhammadiyah Ponorogo, 2025)
The spread of fake news (hoaxes) through social media has become a serious challenge in Indonesia due to its impact on social stability and national security. This study aims to explore various types of hoaxes circulating on social media, the legal frameworks used to address them, and the role of society in preventing their spread. This research employs a qualitative approach through document analysis of relevant regulations, such as the Electronic Information and Transactions Law (UU ITE) and the Indonesian Criminal Code (KUHP), as well as case studies of viral hoaxes in Indonesia. The findings indicate that hoaxes can be categorized into several types, including hate speech based on ethnicity, religion, race, and intergroup relations (SARA), public fraud, defamation, and false information that causes panic. Health-related hoaxes have also become a significant concern, particularly during the pandemic. Law enforcement against hoax perpetrators must be carefully implemented to avoid violating freedom of speech. Therefore, digital literacy is essential to raise public awareness in identifying and preventing the spread of hoaxes.